2013
DOI: 10.1111/1567-1364.12030
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life cell cycle arrest contributes to stochasticity of yeast replicative aging

Abstract: There is growing evidence that stochastic events play an important role in determining individual longevity. Studies in model organisms have demonstrated that genetically identical populations maintained under apparently equivalent environmental conditions display individual variation in lifespan that can be modeled by the Gompertz-Makeham law of mortality. Here we report that within genetically identical haploid and diploid wild type populations, shorter-lived cells tend to arrest in a budded state, while cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 59 publications
5
23
0
Order By: Relevance
“…For example, researchers found that delays in nuclear segregation during cytokinesis occur rarely during a cell’s lifetime but increase dramatically in frequency after division speeds slow with age 32 . Researchers also correlated heterogeneity in end-state cell morphology, which had been previously reported by microdissection studies 38,39 , with molecular properties of those cells. Cells trapped under a PDMS column that die in a round (as opposed to elongated) morphology are shorter-lived, display more pronounced measures of mitochondrial dysfunction, and have higher Hsp104 promoter activity at death 9,10 .…”
Section: Discoveriesmentioning
confidence: 66%
“…For example, researchers found that delays in nuclear segregation during cytokinesis occur rarely during a cell’s lifetime but increase dramatically in frequency after division speeds slow with age 32 . Researchers also correlated heterogeneity in end-state cell morphology, which had been previously reported by microdissection studies 38,39 , with molecular properties of those cells. Cells trapped under a PDMS column that die in a round (as opposed to elongated) morphology are shorter-lived, display more pronounced measures of mitochondrial dysfunction, and have higher Hsp104 promoter activity at death 9,10 .…”
Section: Discoveriesmentioning
confidence: 66%
“…Given our recent findings of a correlation between short lifespan and S phase arrest in yeast terminal state (Delaney et al, 2013), it seems highly unlikely that a defect in DNA replication via reduced Isw2 would promote longevity.…”
Section: Resultsmentioning
confidence: 96%
“…Rad53 has been previously implicated in aging (Delaney et al, 2013; Schroeder et al, 2013; Weinberger et al, 2010) but not linked to the response to DR. Redistribution of Los1 to the cytoplasm in response to DR was prevented in cells lacking RAD53 (p=0.1, Figure 4A, Supplemental Table S5, related to Figure 4).…”
Section: Resultsmentioning
confidence: 99%